Hadith Book of Middle Age : The Study of Al-Targīb Wa Al-Tarhīb Book by Al-Munżirī - Muhammad Anshori (Universitas Islam Negeri (UIN) Salatiga, 2019)
This paper attempts to describe and analyze one of the anthologies or secondary hadith books of medieval, namely al-Targīb wa al-Tarhīb by al-Munżirī (581-656 H). This book has quite a lot of hadith, so it is natural that the quality is varied, sahih, hasan, and daif (with various forms). Al-Targīb wa al-Tarhīb can be categorized as a book of adab or morality of a Muslim that can be a provision of life in the world and the hereafter. The Hadiths contained in the book contain quite complex themes or topics, ranging from life in the world and the hereafter. But what is certain is that the book al-Targīb wa al-Tarhīb was written not at the initiative of al-Munżirī himself, but was a request from one of his students. After praying or asking God for guidance, some time later he was willing to write the book. Al-Munżirī did not just include the quoted hadiths, but also gives an assessment and explains the words that are considered difficult to be understood. Thus, he has also conducted research on hadith.